UHRF1 overexpression is involved in cell proliferation and biochemical recurrence in prostate cancer after radical prostatectomy. Issue 1 (December 2016) - Wan, Xuechao; Yang, Shu; Huang, Wenhua; Wu, Denglong; Chen, Hongbing; Wu, Ming; Li, Junliang; Li, Tao; Li, Yao
Abstract Background Biochemical recurrence (BCR) is widely used to define the treatment success and to make decisions on if or how to initiate a secondary therapy, but uniform criteria to define BCR after radical prostatectomy (RP) is not yet completely assessed. UHRF1 has a unique function in regulating the epigenome by linking DNA methylation with histone marks. The clinical value of UHRF1 in PCa has not been well done. Therefore, we evaluated the prognostic significance of UHRF1. Method UHRF1 expression in PCa cells was monitored by qRT-PCR and Western blot analyses. UHRF1 expression was knocked down using specific siRNAs, and the effects of knockdown on the proliferation, migration, cell cycle, and apoptosis of PCa cell lines were investigated. UHRF1 protein expression was evaluated in 225 PCa specimens using immunohistochemistry in tissue microarrays. Correlations between UHRF1 expression and the clinical features of PCa were assessed. Results The results showed that UHRF1 was overexpressed in almost all of the PCa cell lines. In PCa cells, UHRF1 knockdown inhibited cell proliferation and migration, and induced apoptosis. UHRF1 expression levels were correlated with some clinical features of PCa. Multivariate analysis showed that UHRF1 expression was an independent prognostic factor for biochemical recurrence-free survival. Conclusions UHRF1 functions as an oncogene in prostate cancer and appears to be capable of predicting the risk of biochemical recurrence in PCa patients after radical prostatectomy, and may serve as a potential therapeutic target for PCa.